Effect of Intravitreal Anti-Vascular Endothelial Growth Factor Injection on Intraocular Pressure and Systemic Blood Pressure - Saleem, Beenish; Khizer, Muhammad Azeem; Khan, Asfandyar; Sarfraz, Muhamamd Haroon; Muhammad, Shoaib; Ali, Dilshad (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the effect of intravitreal anti-vascular endothelial growth factor injections on intraocular pressure and systemic blood pressure in the immediate post-injection period. Study Design: Quasi-experimental study. Place and Duration of Study: Armed Forces Institute of Ophthalmology, Rawalpindi Pakistan, from Aug 2020 to Jan 2021. Patients and Methods: Patients over the age of 21 years receiving the first anti-vascular endothelial growth factor injection for various retinal vascular disorders were included in the study. Intraocular pressure (measured with Tono-pen) and systemic blood pressure were recorded 5 minutes before (baseline) and after, as well as 30 minutes after intravitreal injection. Results: One hundred and thirty-two patients were included in the study. The median intraocular pressure value in the study population was 14.00 (5) mmHg, while median systolic and diastolic blood pressure values were 147.00 (27) mmHg and 86.00 (19) mmHg, respectively. There was a significant rise in median intraocular pressure up to 29.00 (10) mmHg after 5 minutes and up to 29.00 (9) mmHg after 30 minutes (p≤0.001). Similarly, systolic blood pressure was elevated up to 160.00 (25) mmHg at 5 minutes and 151.00 (32) mmHg after 30 minutes (p≤0.001). No statistically significant correlation between intraocular pressure and blood pressure was seen (p=0.156). Conclusion: Intravitreal anti-vascular endothelial growth factor injections are associated with a significant rise in intraocular pressure and blood pressure in the immediate post-injection period, so the patients need to be monitored during this period to avoid any ocular or cardiovascular complications.